Composition of the essential oil of Teucrium parviflorum L. (Lamiaceae) from Turkey - Bagci, Eyup; Hayta, Sukru; Yazgin, Ayse; Dogan, Gulden (Academic Journals, 2011)
The essential oil of the aerial parts of Teucrium parviflorum L. (Lamiaceae) from Turkey was analyzed by GC and GC/MS system. The oil was obtained by hydrodistillation with clevenger apparatus. Thirty three components, representing (80.7%) of the oils, were characterized. The main components were beta-caryophyllene (18.6%), germacrene D (9.2%), caryophyllene oxide (8.8%) and bicyclogermacrene (6%). The results were discussed with the genus pattern in means of medicinal purpose and natural products.
Keywords: Teucrium parviflorum; lamiaceae; essential oil; beta-caryophyllene; germacrene D